Makey Makey and its Possible Application in Libraries - Chaves Arias, Itza (2017)
This bibliographical review presents the concept of Makey Makey as a device born from the maker movement that can be used in the information units. Because of this a revision of works and papers took place in which the historical context of the emergence of this technological resource is develop. In the operating section the main characteristics and uses of the device are described. Also in society and in the information units the Makey Makey has different characteristics for its use in various services, for this it describes the potential use that can have on the part of the professionals in the information.